Cloud accounting is a new prospect for accounting organization - Wissam Aziz shnawa; Hussein kareem mohammed (Journal of Madenat Alelem University College, 2019)
Cloud accounting is one of the most important factors that assist economic units in Keep up of scientific and technological development and its exploitation in the organization of accounting work based on the Internet on the basis of systems designed to carry out all the accounting procedures of the economic unit, The importance of research through cloud accounting in reducing costs through the lack of the need for specialized cadres of accountants and the cost of providing them with places and salaries and training, Because cloud accounting makes all accounting processes very efficient, The research aims to review the concept of cloud accounting and its advantages, The research found that reliance on cloud accounting contributes to cost reduction as well as its contribution to the organization of accounting work, The research recommends relying on cloud accounting and reaping the benefits of it.